Introduksi Produksi Nugget PasTa untuk Diversifikasi dan Inovasi Pangan dari Ampas Tahu pada UKM Tahu Makmur - Dian Rachmawanti; Endi Irfan Aryanto; Gusti Fauza; Dimas Rahadian Aji Muhammad (STKIP Andi Matappa, 2021)
Tahu Makmur is a small medium enterprise (SME) located in Wonosari-Klaten, Central Java Province. Currently, the SME produces ± 5,000 fried tofu per day. Unfortunately, this production activity leaves a lot of tofu dregs that are wasted. Whereas 100 g of tofu dregs still contains 26.6 g of protein and 41.3 g of carbohydrates, meaning that this byproduct is still potential to be processed into a good food product. An alternative to utilize tofu dregs is to process it into a nugget. Nugget is a food product which is usually made from chicken or beef as the main raw material. The innovation in making nuggets could be done by replacing the meats with tofu dregs. The introducing the technology for making nugget-tofu dregs based (so called: 'PasTa nugget') to Tahu Makmur aims to increase its effectiveness and productivity. Tofu dregs that were previously not utilized will be processed into innovative nuggets that have better economic value. The activities are carried out during August-November 2021 through three stages, namely 1) observation and socialization of the PasTa nugget formula to Tahu Makmur, 2) nugget making practices, 3) calculating the cost of goods manufactured (COGs). From this activity, the process of making PasTa nuggets has been introduced to SME Tahu Makmur as well as the COGs has been calculated to help the SME estimates the feasibility of this PasTa nugget business from the financial perspective. From the calculation of fix cost and variable cost, the COGs for the product is 7,686 IDR. Assuming a sales profit margin around 60%, the selling price of PasTa nuggets will be 13,000 IDR, - per 200 g package. The price is quite competitive compared to similar products sold in the market.